2012
DOI: 10.1519/jsc.0b013e31824b4d5b
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Customized Over-the-Counter Mouth Guard on Neuromuscular Force and Power Production in Trained Men and Women

Abstract: Although mouth guards were originally designed for injury prevention, even elite athletes are now using performance mouth guards to improve athletic success. Both expensive custom models and over-the-counter models are available, but the efficacy is not well known. Some athletes remain wary of the perceived potential for detriments using a mouth guard to their performance. Thus, the purpose of this study was to examine various physical performance tests when using a mouth guard including a customized over-the-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 37 publications
4
88
0
4
Order By: Relevance
“…Le paramètre mesuré est la puissance maximale (Peak Power, PP). Des études montrent que le port d'un protège-dents de performance permet d'augmenter le PP mais aussi de l'atteindre plus rapidement et de le maintenir plus longtemps [9,17,18]. Cependant des résultats contraires ont également été publiés [19,20].…”
Section: Fig 3 Different Types Of Under Armour Performance Mouthweaunclassified
See 1 more Smart Citation
“…Le paramètre mesuré est la puissance maximale (Peak Power, PP). Des études montrent que le port d'un protège-dents de performance permet d'augmenter le PP mais aussi de l'atteindre plus rapidement et de le maintenir plus longtemps [9,17,18]. Cependant des résultats contraires ont également été publiés [19,20].…”
Section: Fig 3 Different Types Of Under Armour Performance Mouthweaunclassified
“…ont montré que le port de protège-dents de performance, réalisés selon les principes de la dentisterie neuromusculaire ou des dispositifs MORA, permettait d'améliorer les performances musculaires [3,4,16,17,[53][54][55] que ce soit en termes de :…”
Section: Approche Commune (Neuromusculaire Et Posturale)unclassified
“…Stock and self-adapted MGs are purchased over the counter, whereas custom-made MGs are made from a dental mold by a dentist or orthodontist 14,15,16,17 . If not enforced, most high school athletes choose not to wear any type of MG during either practice or competition 13,18 .…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…However, it has been found that when using self-adapted MGs, there is no difference in respiratory function, regardless of exercise intensity 6,14,18 . It also has been established through a number of studies that there are no performance decrements in any physiological parameter when a customized MG is used 6,7,14,17,18,20 .…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation